2006
DOI: 10.1111/j.1532-5415.2006.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Longitudinal Study of the Functional Status and Quality of Life of Older Patients with Breast Cancer Receiving Adjuvant Chemotherapy

Abstract: Despite toxicity from adjuvant chemotherapy, this cohort of relatively young older patients maintained their functional status and QOL from before chemotherapy to 6 months postchemotherapy. Subtle changes in higher-order functioning would require assessment using different geriatric assessment tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 53 publications
4
46
1
2
Order By: Relevance
“…will superimpose on the geriatric profile of the patient, thereby further compromising prognosis. It has been shown that CGA adds useful information to the evaluation of the World Health Organization-Eastern Cooperative Oncology Group performance status in older patients with cancer and is able to predict efficacy and tolerance of chemotherapy [14,19]. Geriatric instruments appear more sensitive than classic oncological instruments in measuring functional status [9].…”
Section: Geriatric Profilementioning
confidence: 99%
“…will superimpose on the geriatric profile of the patient, thereby further compromising prognosis. It has been shown that CGA adds useful information to the evaluation of the World Health Organization-Eastern Cooperative Oncology Group performance status in older patients with cancer and is able to predict efficacy and tolerance of chemotherapy [14,19]. Geriatric instruments appear more sensitive than classic oncological instruments in measuring functional status [9].…”
Section: Geriatric Profilementioning
confidence: 99%
“…An aspect where much less data is available is response and toxicity patterns of patients in intermediate condition that would not fit standard study inclusion criteria, or studies addressing the general population of oncology clinics. Two studies prospectively assessed such a population (18,42). One observed 60 patients with various cancers.…”
Section: Treatment Patterns and Tolerancementioning
confidence: 99%
“…Yet most were able to complete their treatment with little impact on their functional status (43). The other study focused on breast cancer patients (42). Here again, half of the patients experienced toxicity but were able to continue.…”
Section: Treatment Patterns and Tolerancementioning
confidence: 99%
“…The possible impact of geriatric interventions on cancer outcome is unknown, even though some small prospective studies suggest positive effects. 19,20 Nowadays the concept of oncogeriatry is shared by all oncological and geriatric communities around the world. It is interesting to engage in a semantic discussion about the term: is it actually indicate that it is a sub-speciality of oncology (similar to gastrointestinal oncology), whereas 'oncogeriatry' indicates a merge between oncology and geriatrics.…”
Section: The Concept Of Oncogeriatrymentioning
confidence: 99%